2022
DOI: 10.1029/2022jb023961
|View full text |Cite
|
Sign up to set email alerts
|

Source Characteristics and Exacerbated Tsunami Hazard of the 2020 Mw 6.9 Samos Earthquake in Eastern Aegean Sea

Abstract: On 30 October 2020, 11:51 UTC (13:51 local time), a strong and shallow earthquake of Mw 6.9 occurred off the northern coast of Samos Island, the eastern Aegean Sea, close to the Izmir region of Turkey (Figure 1). The focal mechanism of the Samos earthquake, provided by both teleseismic and geodetic information, is as yet ambiguous due to the lack of near-field observation near the epicenter. A north-dipping extensional normal fault with an almost east-west strike was proposed for the mainshock by , while both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…The data quality is quite high without abnormal spikes within the time series. In data processing, we first filled short gaps by linear interpolation, and then applied a fourth-order Butterworth high-pass filter with a corner frequency of 3.5 × 10 −5 Hz (∼8 hr) to remove low-frequency tidal components (Heidarzadeh & Satake, 2013;Hu et al, 2022). We also note properties of the initial wave at the Gazimagusa station in Turkey for wave analysis from Yalcinera et al (2023).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data quality is quite high without abnormal spikes within the time series. In data processing, we first filled short gaps by linear interpolation, and then applied a fourth-order Butterworth high-pass filter with a corner frequency of 3.5 × 10 −5 Hz (∼8 hr) to remove low-frequency tidal components (Heidarzadeh & Satake, 2013;Hu et al, 2022). We also note properties of the initial wave at the Gazimagusa station in Turkey for wave analysis from Yalcinera et al (2023).…”
Section: Methodsmentioning
confidence: 99%
“…However, at Hatay station, the time lag of the maximum tsunami height from the initial arrival reaches 40 hr (Figure 1b). As the location of the station is in the narrow semi‐closed Iskenderun Bay, we suppose the long delayed maximum waves may be due to tsunami resonance, a coupling of similar period ranges between the Bay's fundamental natural oscillation and source period band (Hu et al., 2022; Satake et al., 2020). We calculate the fundamental oscillation of the Bay based on a semi‐parabolic depth profile with T=2.22×2L/(italicgH) $T=2.22\times 2L/\sqrt{(\mathit{\text{gH}})}$ ( H is the water depth at the entrance of the Bay, L is the length of the Bay) (Wilson, 1972), in which we set H of 60–80 m and L of 60–70 km based on the bathymetry data set.…”
Section: Different Tsunami Properties Inside and Outside The Iskender...mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the active structures in the eastern and northeastern Aegean accommodate significant strain and are associated with elevated earthquake hazard. This increased strain accumulation was notoriously expressed the previous years by the occurrence of the 2017 M w 6.3 Lesvos and M w 6.6 Kos earthquakes (e.g., Kiratzi, 2018; Konca et al., 2019; Sboras et al., 2020) and the 2020 M w 7.0 Samos earthquake (e.g., Chousianitis & Konca, 2021; Hu et al., 2022; Sboras et al., 2021).…”
Section: Quantification Of Geodetic Deformation Ratesmentioning
confidence: 98%
“…Adequate quantification of tsunami risk on populated seashores is a theoretical and practical problem in the Earth sciences. The consequences of the tsunamis in the Indian Ocean in 2004, Tohoku, Japan, in 2011, Sulawesi, Indonesia, in 2018, and the Aegean Sea in 2020 showed that the underestimating of this hazard has led to catastrophic longterm effects for coastal populations, the economy, and the environment [1][2][3][4]. The lack of reliable historical data on tsunami occurrences, characteristic of many coasts, stimulated the development of methods for assessing the tsunami hazard and the risk based on information about the seismic activity described in the scientific literature [5][6][7], as well as magnitude scales for tsunamis [8].…”
Section: Introductionmentioning
confidence: 99%